The meaning of digital era public communication using Luhmann’s system theory: a case study of Central Java Provincial Government, 2018-2022 - Sholikhah, Nur Imroatus; Wahyuni, Hermin Indah; Rahayu, Rahayu (International Journal of Communication and Society, 2025)
This study explores the meaning of public communication by Indonesia’s local governments in response to digital environment. The research aims to examine how local government public communication systems adapt through their meaning of the digital landscape. Grounded in Niklas Luhmann's social system theory, which posits meaning as a stimulus for systems to respond to environmental changes, this study views meaning as the energy that enables a system to autonomously select its needs and methods (autopoiesis) for adaptation. Autopoiesis responds to meaning through three processes: communication (social dimension), evolution (temporal dimension), and differentiation (functional dimension). The meaning stimuli in this study will be explained in terms of their potential for enabling the system to perform autopoiesis. The research employs a case study of the meaning of digital-era public communication by the Central Java Provincial Government (Pemprov Jawa Tengah). Operationally, the meaning is examined by observing how Pemprov Jawa Tengah gives meaning to the digital era and depicts its public communication landscape throughout 2018-2019. Data is collected through interviews and documentation of statements made by Pemprov Jawa Tengah in online media. The results indicate that the social dimension of giving meaning to public communication by local governments in the digital era influences the system's considerations through interactions with the political system, e-government system, information technology system, and media system. In the temporal dimension, the developed meaning will impact public communication systems in three phases: dissemination phase 1 (2018-2019), responsive phase (2020-2021), and dissemination phase 2 (2022). These three phases in the evolutionary dimension elucidate the meaning conducted by local governments, dominated by considerations of the public communication function for quickly responding to public service complaints, strengthening performance reputation, and enhancing the popularity of local government’s leaders.